Pulau Layang-Layang in Malaysia’s South China Sea policy: Sovereignty meets geopolitical reality amid China–U.S. rivalry - Lai yew meng; Kuik Cheng-Chwee; Amy Azuan Abdullah (International Journal of China Studies, 2021)
Pulau Layang-Layang (Swallow Reef) is central to Malaysia’s South China Sea policy. First, the “island” is the first of five features in the South China Sea occupied by Malaysia. Second, since 1983, by exercising exclusive and effective control over Layang Layang, Malaysia has displayed its sovereignty and jurisdiction over the area. Third, with a Malaysian naval station and airstrip, Layang-Layang is Malaysia’s most valuable strategic asset in the South China Sea. Drawing on archival materials and open sources, this paper traces Malaysia’s policy actions vis-à-vis Pulau Layang-Layang, before unpacking the features and factors underpinning the smaller state’s multi- pronged approaches towards the South China Sea disputes. We argue that Malaysia’s policies regarding Pulau Layang-Layang and the broader South China Sea issue have been and will continue to be driven by small-state pragmatism to balance national sovereignty and geopolitical reality amid the growing U.S.–China rivalry.